ANALISIS PAJAK DAN RETRIBUSI DAERAH PADA TINGKAT EFEKTIVITAS DAN KEMANDIRIAN KEUANGAN DAERAH - Ramadhan S., Aditya; M. Ratna Sari, Maria (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
The purpose of this research was to determine the contribution of local taxes and retribution on revenue as well as the level of effectiveness and Regional Financial Independence the government of Denpasar. This research was conducted for the period of 2009-2013. This research is a quantitative descriptive research. Based on the analysis determine that local taxes are the main revenue component in local revenues which reached an average of 72% annually and followed by the retribution whiich contribute an average of 8% annually. The level of effectiveness of local government revenue Denpasar when averaged over the 2009-2013 fiscal year amounted to 121.45% with a very effective assessment criteria. The ratio of the level of financial independence Denpasar city area during the period of the fiscal year 2009-2013 was 64% with very good assesment criteria.
Keywords: Local Tax, Retribusion, Financial Independency, Financial Effectiveness